Stethorus spp. (Coleoptera: Coccinellidae) predatory on Schizotetranychus hindustanicus (Hirst) (Acari: Tetranychidae) from South India, including a new species and a new synonymy in Indian Stethorus - Poorani, J. (Zootaxa, 2017)
Stethorus forficatus sp. nov. and Stethorus tetranychi Kapur (Coccinellidae: Stethorini) are reported as predators of the citrus hindu mite, Schizotetranychus hindustanicus (Hirst), from the southern Indian state of Tamil Nadu. Stethorus forficatus sp. nov. is described and illustrated with diagnostic notes on S. tetranychi and S. vietnamicus Hoàng, morphologically its closest relatives. In a remarkable case of larval mimicry in Stethorus, the larva of this species mimics the larvae of S. tetranychi and S. pauperculus Weise. Stethorus curvus Hoàng, 1985 is reduced to a new junior synonym of Stethorus keralicus Kapur, 1961 (syn. nov.).